Alterations of state : sacred kingship in the English Reformation - McCoy, Richard C., 1946- (Columbia University Press, 2002)
During the English reformation, writers like John Skelton, Shakespeare, John Milton, and Andrew Marvell grappled with the idea of kingship and royalty, its real presence and figurative power. McCoy explains why religious devotion to the royal person became both more acute and more problematic during England's turbulent seventeenth century.